Development of macaronic Hindi-English 'Hinglish' text message content for a coronary heart disease secondary prevention programme. Issue 2 (30th September 2016) - Thakkar, Jay; Karthikeyan, Ganesan; Purohit, Gaurav; Thakkar, Swetha; Sharma, Jitender; Verma, Sunilkumar; Parakh, Neeraj; Seth, Sandeep; Mishra, Sundeep; Yadav, Rakesh; Singh, Sandeep; Joshi, Rohina; et al.
Abstract : Background: Coronary heart disease (CHD) is a leading cause of morbidity and mortality in India. Text message based prevention programs have demonstrated reduction in cardiovascular risk factors among patients with CHD in selected populations. Customisation is important as behaviour change is influenced by culture and linguistic context. Objectives: To customise a mobile phone text message program supporting behaviour and treatment adherence in CHD for delivery in North India. Methods: We used an iterative process with mixed methods involving three phases: (1) Initial translation, (2) Review and incorporation of feedback including review by cardiologists in India to assess alignment with local guidelines and by consumers on perceived utility and clarity and (3) Pilot testing of message management software. Results: Messages were translated in three ways: symmetrical translation, asymmetrical translation and substitution. Feedback from cardiologists and 25 patients was incorporated to develop the final bank. Patients reported Hinglish messages were easy to understand (93%) and useful (78%). The software located in Australia successfully delivered messages to participants based in Delhi-surrounds (India). Conclusions: Our process for customisation of a text message program considered cultural, linguistic and the medical context of potential participants. This is important in optimising intervention fidelity across populations enabling examination of the generalisability of text message programs across populations. We also demonstrated the customised program was acceptable to patients in India and that a centralised cross-country delivery model was feasible. This process could be used as a guide for other groups seeking to customise their programs. Trial registration number: TEXTMEDS Australia (Parent study)—ACTRN 12613000793718.